Effects of Various Grazing Systems on Grazing and Subsequent Finishing Performance - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 240 mixed black yearling steers were used to compare grazing and subsequent finishing performance from pastures with ‘MaxQ’ tall fescue, a wheat-bermudagrass double-crop system, or a wheat-crabgrass double-crop system in 2010, 2011, 2012, 2013, 2014, and 2015. Daily gains of steers that grazed MaxQ fescue, wheatbermudagrass, or wheat-crabgrass were similar (P>0.05) in 2010. The daily gains of steers that grazed wheat-bermudagrass or wheat-crabgrass were greater (P>0.05) than those that grazed MaxQ fescue in 2011 and 2012. The daily gains of steers that grazed wheat-crabgrass were greater (P>0.05) than those that grazed wheat-bermudagrass and similar (P>0.05) to those that grazed MaxQ fescue in 2013. The daily gains of steers that grazed wheat-crabgrass were greater (P>0.05) than those that grazed wheatbermudagrass or MaxQ fescue in 2014, and daily gains of steers that grazed wheatcrabgrass were greater (P>0.05) than those that grazed wheat-bermudagrass or MaxQ fescue and daily gain from wheat-bermudagrass was greater (P>0.05) than those that grazed MaxQ fescue in 2015. Finishing gains were similar (P>0.05) among forage systems in 2010, 2012, 2013, and 2014. Finishing gains of steers that grazed MaxQ fescue were greater (P<0.05) than those that grazed wheat-bermudagrass in 2011 and greater (P<0.05) than those that grazed wheat-bermudagrass or wheat-crabgrass in 2015.
Keywords: Beef cattle